2023
DOI: 10.3389/fonc.2023.1242392
|View full text |Cite
|
Sign up to set email alerts
|

New research progress on 18F-FDG PET/CT radiomics for EGFR mutation prediction in lung adenocarcinoma: a review

Xinyu Ge,
Jianxiong Gao,
Rong Niu
et al.

Abstract: Lung cancer, the most frequently diagnosed cancer worldwide, is the leading cause of cancer-associated deaths. In recent years, significant progress has been achieved in basic and clinical research concerning the epidermal growth factor receptor (EGFR), and the treatment of lung adenocarcinoma has also entered a new era of individualized, targeted therapies. However, the detection of lung adenocarcinoma is usually invasive. 18F-FDG PET/CT can be used as a noninvasive molecular imaging approach, and radiomics c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…Previous research has shown that radiomic features extracted from PET/CT and CT images can predict gene expression patterns and EGFR mutation status [ 14 , 36 ]. In their review, Ge et al [ 37 ] highlighted that machine learning-based radiomics (MLR, specifically shallow learning), have demonstrated high accuracy in predicting EGFR mutations. The advantage of CT_TL and PET_TL over the radiomics models in this study was insignificant, possibly due to the small sample size and different patient compositions in the training set.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that radiomic features extracted from PET/CT and CT images can predict gene expression patterns and EGFR mutation status [ 14 , 36 ]. In their review, Ge et al [ 37 ] highlighted that machine learning-based radiomics (MLR, specifically shallow learning), have demonstrated high accuracy in predicting EGFR mutations. The advantage of CT_TL and PET_TL over the radiomics models in this study was insignificant, possibly due to the small sample size and different patient compositions in the training set.…”
Section: Discussionmentioning
confidence: 99%